Effectiveness of peer group-based learning in enhancing elementary students’ knowledge of larval monitoring in Banda Aceh - Hermansyah, Hermansyah; Susanti, Helly (Poltekkes Kemenkes Aceh, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a major public health concern in Indonesia, with over 143,000 cases and an incidence rate of 51,5 per 100,000 population reported in 2023. Recurrent outbreaks in Banda Aceh highlight the need for sustainable, school-based prevention strategies. School-age children are highly vulnerable because Aedes aegypti mosquitoes bite during the daytime when children are at school.Objectives: This study evaluated the effectiveness of elementary school peer groups in improving students’ knowledge of dengue prevention through a school-based larval monitoring program.Methods: A quasi-experimental pre–post design was conducted from April to October 2024 among fourth and fifth grade students in six elementary schools in the Kutaraja Sub-district, Banda Aceh City. Guided by Bandura’s Social Learning Theory, 36 students were trained as peer educators to teach 120 peers (n = 120) about dengue prevention. Knowledge was measured using a 15-item Guttman scale questionnaire before and after the intervention. Data were analyzed using SPSS, including descriptive statistics, Kolmogorov–Smirnov normality tests, and paired t-tests (α = 0,05; 95% CI).Results: The mean knowledge score increased from 9,43 (SD = 1,27) to 10,16 (SD = 1,34), a significant improvement (mean difference = 0,73; 95% CI: 0,41–1,05; p < 0,001).Conclusion: Peer-group–based health promotion within schools is a promising approach to enhance dengue prevention awareness among children. Strengthening teacher facilitation and embedding structured peer education into school health programs may enhance long-term community participation in dengue prevention and control.